Multi-criteria decision analysis for assessment and appraisal of orphan drugs - Georgi Iskrov; Georgi Iskrov; Tsonka Miteva-Katrandzhieva; Tsonka Miteva-Katrandzhieva; Rumen Stefanov; Rumen Stefanov (Frontiers Media S.A., 2016)
Background: Limited resources and expanding expectations push all countries and types of health systems to adopt new approaches in priority setting and resources allocation. Despite best efforts, it is difficult to reconcile all competing interests and trade-offs are inevitable. This is why multi-criteria decision analysis (MCDA) has played a major role in recent uptake of value-based reimbursement. MCDA framework enables exploration of stakeholders' preferences, as well as explicit organization of broad range of criteria on which real-world decisions are made.Assessment and appraisal of orphan drugs tend to be one of the most complicated health technology assessment (HTA) tasks. Access to market approved orphan therapies remains an issue. Early constructive dialogue among rare disease stakeholders and elaboration of orphan drug-tailored decision support tools could set the scene for ongoing accumulation of evidence, as well as for proper reimbursement decision-making.Objective: The objective of this study was to create a MCDA value measurement model to assess and appraise orphan drugs. This was achieved by exploring the preferences on decision criteria's weights and performance scores through a stakeholder-representative survey and a focus group discussion that were both organized in Bulgaria.Results/Conclusions: Decision criteria that describe the health technology's characteristics were unanimously agreed as the most important group of reimbursement considerations. This outcome, combined with the high individual weight of disease severity and disease burden criteria underlined some of the fundamental principles of healthcare - equity and fairness. Our study proved that strength of evidence may be a key criterion in orphan drug assessment and appraisal. Evidence is not only used to shape reimbursement decision-making, but also to lend legitimacy to policies pursued. The need for real-world data on orphan drugs was largely stressed.Improved knowledge on MCDA feasibility and integration to HTA is of paramount importance, as progress in medicine and innovative health technologies should correspond to patient, healthcare system and societal values.